Gender disparities in altmetric attention scores for cardiovascular research - Lerchenmüller, Marc; Schmallenbach, Leo; Bley, Maximilian; Lerchenmüller, Carolin (Communications biology, 2023)
Analysis of the association between Altmetric scores and the gender of first and last authors of articles published in top cardiovascular research journals shows that women receive on average less attention for their work.